2013
DOI: 10.11648/j.ab.20130105.12
|View full text |Cite
|
Sign up to set email alerts
|

Endo-N-Acetyl-β-D-Glucosaminidases and Peptide-N4-(N-acetyl-β-D-Glucosaminyl) Asparagine Amidases: More Than Just Tools

Abstract: Abstract:Since the discovery of endo-N-acetyl-β-D-glucosaminidases (ENGase) and peptide-N4-(N-acetyl-β-D-glucosaminyl) asparagine amidases (PNGase) most of the published work described their use for structural studies. Less attention was given to the potential roles of those enzymes in the physiology of the cells/organisms they produced them. The scope of this review is firstly to analyse the data on the occurrence and characteristics of murein-, chitin-, and N-glycan-ENGases acting on GlcNAc-containing polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 189 publications
0
1
0
Order By: Relevance
“…Endo F3 is known to cleave a wide variety of complex glycans, but not oligomannose and hybrid structures and has 400-fold lower activity on nonfucosylated glycans . Indeed, we found that upon incubation of trastuzumab with endo F3, the majority of glycans was readily removed, but full trimming was not attained, even with large excess of enzyme.…”
Section: Resultsmentioning
confidence: 80%
“…Endo F3 is known to cleave a wide variety of complex glycans, but not oligomannose and hybrid structures and has 400-fold lower activity on nonfucosylated glycans . Indeed, we found that upon incubation of trastuzumab with endo F3, the majority of glycans was readily removed, but full trimming was not attained, even with large excess of enzyme.…”
Section: Resultsmentioning
confidence: 80%